Os limites da autonomia do paciente e a arquitetura da escolha - Lima, Andrei Ferreira de Araújo (2022)
The present thesis, concerned with the overrating of the principle of autonomy in the field of Bioethics, especially in relation to the principlist current, aims to deepen the theme in order to clarify the limits of the decision-making power of the patient, avoiding a resumption of the medical paternalism or the suppression of autonomy. Despite the fair criticisms addressed to Bioethics based on autonomy and, consequently, to the Kantian postulates, which are in a large extent the foundations of that current, the present thesis defends the maintenance of the logic of the Prussian philosopher's maxims, that is, it defends that autonomy (capacity for self-determination) is the foundation of dignity, and that dignity is directly linked to the concept of the human being, always as an end in itself and never simply as a mean. On the other hand, the critics cannot be ignored, especially those coming from neuroscience which, based on behavioral economics studies, have proven that human beings often unconsciously act against their own interests, that is, the belief in human rationality must be reviewed. In this sense, the current research defends the insertion of the concept of the architecture of choice and the ethics of influence, both linked to libertarian paternalism, in the hospital environment and in the doctor-patient relationship. The concepts aim to help subjects to make the best decisions according to their best interests, promoting dialogue between those involved in the environment. It is argued that the architecture of choice is the right measure to harmonize patient autonomy with the medical paternalism. The limits to autonomy will be established even before the architecture is formulated, leaving, then, only the ethically and legally applicable options. The doctor, in this second moment, will be responsible for promoting influence so that the patient chooses the most effective treatment, leaving him, however, free to choose other possibilities or even refuse them, promoting his autonomy, respecting his dignity, treating him as an end in itself.